(NqZYK I WNEQZYKOWAQ DEJSTWITELXNOSTX (B:s (NoPYT ONTOLOGI^ESKOGO SRAWNENIQ (B/s - d ((NeREWAN (B:s (Negu(B,s, 1987)
(NbIBLIOGR(B. (NW PRIME^(B.: (NS(B. 296-381s
Keywords: (NsEMIOTIKAs; (NqZYK I MY[LENIEs